ORGANIZATION OF SUMMER HEALTH AND CONDITIONING OF CHILDREN IN PRESCHOOL EDUCATIONAL ORGANIZATIONS - Botirova Latofat Luftillayevna (American Journals, 2023)
The article reveals ways to organize summer wellness and conditioning work with children in preschool educational organizations, planning and organizing educational activities, physical development and the formation of a healthy lifestyle in development centers and general groups that are carried out during the academic year during the summer season.
Keywords: frontal, mental and mental development, sports inventory, adaptation groups, integration.